i-Clo smart dryer closet / Siti Nur Ezzaty Kamar Baharin...[et al.] - Kamar Baharin, Siti Nur Ezzaty; Zailani, Amira Sakina; Abdul Rahim, Muhammad Amiruddin; Md Nasri, Muhammad Shamir; Yusop, Kamil Harith (2018)
i-CIo Smart Dryer Closet will get your day become easy and efficient. I-CIo is a concept of simplify your day life. Nowadays, there are various innovations carried out with existing product. It produces billion throughout the world and still growing from days to days. Our I-CIo product is also among the products that we innovate from existing product in market. We had seen to the areas and other industrial in order to gain inspiration for the concept and come out with new innovations. Always we challenge ourselves and question conventional products or production process. After we go through of all those processes, we have come out with the idea for our new product which is I-CIo Smart Dryer Closet. We introduce our latest product where we are innovating our product by putting a temperature controller, timer controller in order to save time and effort by hanger your clothes into the dryer closet and allow it to dry by setting the temperature and timer controller, supportive fan in order to reduce the dampness on the closet. This dryer is also designed to prevent creasing so that it makes the clothes are so much easier to iron. Besides that, I-CIo can solve the problem of having a tidy home especially for high rise building such as apartment, condominium and others. With the size of I-CIo that we have designed, it will suit for group of family who have limited space in their home and want a tidy home. People are also does not need to be worry about the weather because it is really does not a matter whether it going to be a rainy day or not. When you have our dryer closet, you will have warm and dry clothes all years round. The price of our dryer closet is set at a level to become more affordable to our target customer We are also ISO9002:2000 certified company. Furthermore, we have Product Liability Insurance for all items; it's a double guarantee for customers together with our reliable quality.